Effect of the TPB -based intervention on e-cigarette smoking prevention among elementary school students at Pong Nam Ron District in Chanthaburi Province - Putthai, Piyawadee; Mettakunpitak, Nantawat; Homman, Jitthranuch; Srisuriyawet, Rungrat (Thai Journal of Nursing, 2025)
The objective of this quasi-experimental study was to examine effect of the TPB -based intervention on e-cigarette smoking prevention among elementary school students at Pong Nam Ron district in Chanthaburi province. Participants were male and female students, 5- 6th grade, 62 students were purpossively selected and equally divided into the experimental group received TPB -Based Intervention consisted of a four-session intervention and 4 weeks follow- up and the comparative group attended regular classes. Data were collected using questionnaires. The two-way repeated -measures ANOVA was used in data analysis. Results reveal that at post-test and follow-up peroids, the experimental group had an average score of anti- smoking attitudes towards e-cigarette, e-cigarette vaping refusal self-efficacy, and intention to denied vaping higher than those at pre-test and the comparative group at p < .001 (F = 30.714, F = 56.531 and F = 126.123, respectively).